2018
DOI: 10.1103/physreva.98.053442
|View full text |Cite
|
Sign up to set email alerts
|

R -matrix-with-time-dependence theory for ultrafast atomic processes in arbitrary light fields

Abstract: We describe an ab initio and non-perturbative R-matrix with time-dependence theory for ultrafast atomic processes in light fields of arbitrary polarization. The theory is applicable to complex, multielectron atoms and atomic ions subject to ultrashort (particularly few-femtosecond and attosecond) laser pulses with any given ellipticity, and generalizes previous time-dependent R-matrix techniques restricted to linearly polarized fields. We discuss both the fundamental equations, required to propagate the multie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 116 publications
1
47
1
Order By: Relevance
“…More recently, it has been found that photoelectron momentum distributions arising from such pulses carry novel signatures of wave-particle duality. Indeed, as predicted theoretically [41,54], and demonstrated experimentally [55,56], the distributions typically contain multi-armed spirals, caused by the interference between outgoing electron wavepackets with different magnetic quantum numbers. Here we investigate the response of a truly multielectron target, Ar, to counter-rotating circularly polarized pulses.…”
Section: Arbitrarily Polarized Lightmentioning
confidence: 59%
“…More recently, it has been found that photoelectron momentum distributions arising from such pulses carry novel signatures of wave-particle duality. Indeed, as predicted theoretically [41,54], and demonstrated experimentally [55,56], the distributions typically contain multi-armed spirals, caused by the interference between outgoing electron wavepackets with different magnetic quantum numbers. Here we investigate the response of a truly multielectron target, Ar, to counter-rotating circularly polarized pulses.…”
Section: Arbitrarily Polarized Lightmentioning
confidence: 59%
“…Further calculations (not shown) demonstrate that an asymmetry is not apparent in the distribution until the time delay is reduced to around 30 fs, which is well outside the error estimate of the measured delay. This asymmetry induced by ionization pathways involving both pulses is well known, and has been observed and analyzed in previous work [30,52].…”
Section: Resultsmentioning
confidence: 58%
“…RMT has been used to analyze the strong-field dynamics of a variety of atoms and ions, particularly in HHG by noble-gas atoms at near-IR wavelengths [54], strong-field rescattering in F − [55], as well as extreme-ultraviolet-initiated HHG in Ne [56] and Ar + [57]. Recently, RMT calculations of photoelectron momentum distributions for two-photon ionization of helium using counter-rotating circularly polarized pulses [52] were compared against those from time-dependent close-coupling calculations [30]. A further study addressed the influence of the bound-electron magnetic quantum number on detachment yields from F − in circularly polarized pulses [58].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we employ the R-matrix with timedependence (RMT) method [24][25][26][27] to study angular streaking from F − . RMT is an ab initio method that solves the time-dependent Schrödinger equation for multielectron atoms, ions and molecules in strong laser fields.…”
mentioning
confidence: 99%
“…Our treatment of the F − ionic structure is described in previous work [26,28,29], and is based on earlier Rmatrix Floquet calculations for this system [30,31]. To investigate electron correlation in the core, we consider two atomic structure models, one in which the residual F atom is treated at the Hartree-Fock level of detail [32], and another that uses pseudo-orbitals to construct a set of configurations for subsequent use in a configurationinteraction calculation of the 1s 2 2s 2 2p 5 2 P o state of F. We couple a single electron to the residual neutral, retaining all 1s 2 2s 2 2p 5 l channels up to l = L max + 1.…”
mentioning
confidence: 99%